Does intermarriage change migrants' preferences for the home country? - Rosa Weber (IZA Journal of Migration, 2015)
Motivations for migrants to return clearly change with integration, but the time-changing aspect of return migration has received little attention in the literature. This paper studies how migrants' preferences for the home country change with intermarriage, i.e., marriage to a spouse from the host country. Specifically, I analyse the association between intermarriage and three outcomes related to migrants' home country preference - intentions to return, remittances sent and actual return - using German panel data (SOEP) for the period 1984 - 2012. The results reveal a negative association between intermarriage and home country preference that is moreover stronger for female than for male migrants. However, some of the effect seems driven by selection since the relationship gets weaker once I control for person fixed effects.
Keywords: F22; J1; 330; Return migration; Intermarriage; Intentions to return; Remittances